Network Characteristics and Patenting in Biotechnology, 1990-2006 - Demirkan, Irem (2014)
In this study, the authors focus on specifically which types of networks and what types of relationships matter most for the focal firm's innovative performance in biotechnology patenting. They suggest that certain network characteristics, such as quality and the source of knowledge, and the quality of relationships among actors may have a profound effect on the knowledge exchange and hence the number of patents granted to the firm. The authors focus on the research coauthorship networks of 381 firms in the U.S. biotechnology industry over a span of 17 years, from 1990 to 2006. In the biotechnology industry, firms depend heavily on the social network of academic scientists for the exchange and production of knowledge, with firm-level patenting closely linked to it. Their findings largely support the hypotheses, suggesting the necessity to consider the characteristics of the actors and the qualitative nature of the relationships in the network while assessing the role of the firm's networks on its patenting.